The effect of special exercises in the super set style in developing some kinematic variables and achieving javelin throwing for youth - Hameed, RajaaAbdulkareem; KhameesJaber, Khalid; Adnan Khamees, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
The importance of the research came from the serious interest of researchers in this subject to develop some scientific solutions to address this problem by designing explosive strength training in the Super C style and according to the correct sports training foundations that ensure the athlete’s development in proportion to the method of technical and kinetic performance of this effectiveness and with high economics, and this may help the trainers Those interested in this event work to improve the elements of this event in terms of training and technology, and the study aimed to prepare training exercises The explosive power in the super set style for the members of the research sample, as well as the identification of the effect of the explosive power training in the super set style in developing some kinematic variables and the achievement of javelin throwing for youth. The researchers used the experimental method to fit the nature of the problem by designing one experimental group. The research community was determined from the javelin throwers for young people, aged (14-16) years, and their number was (6) from the players of Diyala Governorate clubs registered within the Sub-Athletics Federation, and they were selected The research sample was taken by the intentional method because the objectives of the research require athletes who are good at performing javelin throwing, and the sample represents 100% of the research community. The head of the training unit and it lasted from 45 to 50 minutes at a rate of (3) units per week for a period of (8) weeks, as the number of training units reached (24) units and the duration of the training units was (8) weeks, with two medium courses and (3) training units In one small session, the researchers automatically concluded that the exercises of the super set style had had an effect in improving the level of kinematic variables during the throwing and completion steps through the results obtained and thus obtaining a total strength on it. And transferring it through the parts of the body to the spear at the moment of launch, and this is reflected in the level of achievement. The researchers recommend emphasizing the importance of using exercises and different resistances in the superset, which has a great role in developing physical abilities and to the need to conduct experiments and other applied forms of superset  exercises to develop other physical abilities such as endurance and other abilities They stress the need for those in charge of the training process for young people to know that their physical training is in accordance with mechanical requirements and according to sound scientific foundations.